EFFECT OF BUSINESS RISK, COMPANY SIZE, SALES GROWTH, AND TOTAL ASET TURNOVER AGAINST DEBT TO EQUITY RATIO: Study of Pharmaceutical Sub-Sector Companies Listed on the Indonesia Stock Exchange 2014-2021 Period - Intan Suselo; Ferry Kosadi (Journal of Accounting Inaba, 2023)
The purpose of this study is to determine the effect of business risk, company size, and sales growth Total Asset Turnover Against Debt to Equity Ratio. The method used in this research is a quantitative method with a descriptive and verification approach. The data analysis technique used in this study is the classical assumption, multiple linear regression test, person correlation coefficient test (product moment), test the coefficient of determination (R2), and hypothesis testing both partially (t test) and simultaneously (f test) using the help of the SPSS version 25 program. Based on the research results show that in testing the hypothesis (t test) the results are: (1) Business Risk (DOL) has a significant effect on Debt to Equity Ratio. (2) Company size has no significant effect on Debt to Equity Ratio. (3) Company growth has a significant effect on Debt to Equity Ratio. (4) Total Asset Turn Over has a significant effect on Debt to Equity Ratio. (5) Business Risk, Company Size, Sales Growth, and Total Asset Turn Over provide a simultaneous (together) effect on Debt to Equity Ratio.(6)